Migrants at the Russian labor market: occupations, mobility, intensity of labor and wages - V. I. Mukomel (Статистика и экономика)
The aim of the study is to analyze the extent of the presence of migrants and their behavior in the Russian labor market on the basis of largescale sociological surveys of migrants. This is especially important in the absence of reliable statistics on migrants in the labor market. The main attention is paid to the employment profiles of representatives of various socio-demographic and ethnic groups, illegal and informal employment, the intensity and wages of migrants from countries with a visa-free regime with Russia. Particular attention is paid to labor mobility of migrants. The main empirical basis for analysis was the results of sociological polls conducted by the Center for Ethnopolitical and Regional Studies for the Higher School of Economics in 2011. (8,5 thousand respondents) and in 2017 (8,6 thousand migrants in 19 regions of Russia). The study showed that education, qualifications, professional knowledge of migrants are not in demand on the Russian market, the typical path of migrants in the labor market is downward labor mobility – occupying a job that is worse than previously occupied in the homeland. At the same time, migrants are adapted to changes in the labor market, which is largely facilitated by the differentiation of migrant employment and the vertical mobility of some of them. Innovations in Russian legislation which came into force in 2015, as well as the integration process within the framework of the Eurasian Economic Union (EEA), which greatly facilitated access to jobs in Russia for citizens of the countries of the EEA, had a positive impact on the Russian labor market. The share of illegally employed migrants has significantly decreased in comparison with previous years. At the same time, the problem of informal employment of foreign citizens, excessive exploitation of migrant labor remains. The problems of combating forced labor of migrants and ensuring their decent labor come to the fore. Civilized conditions should be created for the legalization of labor activity of migrants, stimulating their reorientation to integrate into Russian society. The most serious attention should be paid to preventing the social exclusion of migrants to work in Russia, creating effective tools for their secondary socialization and adaptation to Russian realities.